Perlindungan Hukum Terhadap Anak Korban Incest oleh Ayah Kandungnya Perspektif Viktimologi - Ramalia, Yesa Titan; Wahidah, Aisyah Putri (Media Hukum Indonesia (MHI), 2024)
One form of crime that currently threatens children is sexual violence and even rape. However, what happens if the protection that parents should provide to their children in terms of preventing the crime of rape is not provided and instead the parents are the perpetrators of the crime of rape against their own children. The aim of this research is to find out how the regulations provide for the legal protection of children victims of incest rape in Indonesia and to find out what the obstacles are in enforcing legal protection for children victims of biological father incest from a victimological perspective. The research method used with a normative juridical approach is based on the study of (solving existing problems) in positive law. The aspects studied and studied in this research relate to legal protection for child victims of incest and knowing how this problem is studied based on the Viktiomolgi perspective. The conclusions of this research are 1) Legal protection for child victims of incest crimes is carried out by rehabilitating and restoring victims physically, psychologically and socially as well as punishing perpetrators of incest crimes to provide a sense of security to victims 2) obstacles to efforts to enforce legal protection are present from positive law that regulates incest, then from law enforcement officials, as well as from the public who tend to be uncooperative and cover up acts of incest.